Efficacy and Safety of Combine Alfuzosin and Finasteride in the Treatment of Symptomatic Benign Prostatic Hyperplasia: A Quasi-Experimental Study - Siddique, Md Saifuddin Ahmed; Bashar, Sharmin Nahar; Ahmed, Farid Uddin (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2018)
Background: Lower Urinary Tract Symptoms (LUTS) due to Benign Prostatic Hyperplasia (BPH) are common in elder men and a number of drugs alone or in combination are clinically used for this disorder. To assess the efficacy and safety of combined Alfuzosin plus Finasteride, in patients with LUTS due to BHP. Methods: In this hospital-based, Quasi-experimental study (One-Group Pre test-Post test Design) without Control Groups, 30 consecutive patients were selected as per set criteria for medical management of BPH with combination of 10mg Alfuzosin and 5mg Finasteride, for 12-months, in the outpatient Department of Urology, in Chittagong Medical College Hospital. The primary efficacy criteria were improvement in symptoms (International Prostate Symptom Score (IPSS) peak urinary flow rate and reduction of prostate volume from baseline. Results: Combination therapy with Alfuzosin plus Finasteride was effective in improving the symptoms and peak urinary flow rate from the first follow-up visit (Day 90) in comparison to baseline score. The mean change in the IPSS from baseline at endpoint was 10±1.87 (p=0.001). The percentage increase in the peak urinary flow rate was 4.8 mL/s, compared with 11.0±1.82 mL/s at baseline (p=0.001). The patients’ quality of life also significantly improved. The percentage decrease in prostate volume at end point was 15.13±11.3 cc (p=0.001). Overall, this combination therapy was well tolerated. The incidence of orthostatic hypotension as determined by systematic blood pressure measurements was only 3(10%). No clinically relevant ejaculation disorders were observed. Conclusion: Alfuzosin plus Finasteride provides effective relief from the symptoms of benign prostatic hyperplasia by reducing the size of the prostate. It is well tolerated from a cardiovascular viewpoint and is not associated with abnormal ejaculation. Chatt Maa Shi Hosp Med Coll J; Vol.16 (2); July 2017; Page 35-39